If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 8b + -22 = 0 Reorder the terms: -22 + b + 8b = 0 Combine like terms: b + 8b = 9b -22 + 9b = 0 Solving -22 + 9b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 9b = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 9b = 0 + 22 9b = 0 + 22 Combine like terms: 0 + 22 = 22 9b = 22 Divide each side by '9'. b = 2.444444444 Simplifying b = 2.444444444
| 3.5q-3.7-5.8q=-3.3q-3.9 | | 6y+5=5y-3 | | (21/25)(10/117)(27/14) | | 13-2/3x=3 | | 384-1/12 | | (8m-8m-27)(8m-25m-14)=0 | | .3(y)+.14(x)=.18 | | x+4x=58 | | -(3/5)x=(2/5) | | F(9)=100x-5 | | 5x/6-y/3=6 | | 19m=40-17.95 | | 36m^2-49/16=0 | | 37=-2(22-X)+3(X-3) | | (9-3x)(9-5x)= | | -11x^2+3x+11=0 | | 382=x+(x+6) | | (4/11)x=28 | | 3x-108=0 | | 7k-4k=12 | | x+.7=-.2 | | 3x=2(2x-3) | | k/2+5=8 | | s-32=-48 | | v+(v-30.8)+(v+27.3)=202.9 | | 3x^3-7x^2+6x-2=0 | | y^2+2x+8y+13=0 | | 12x^2-24-9=0 | | -7/9x23/4 | | x+(x+6)=382 | | x=-9/2-5/3 | | 4.2/-0.15 |